BROMFENAC VERSUS NEPAFENAC: A STUDY ON MANAGING POST-OPERATIVE CATARACT INFLAMMATION (Journal of Medical & Health Sciences Review, 2025)
Background: Postoperative inflammation is a common complication after cataract surgery. NSAIDs, such as bromfenac and Nepafenac, are commonly used to manage this inflammation due to their safety and effectiveness.Purpose: To compare the efficacy of bromfenac and nepafenac ophthalmic solutions for post-cataract surgery inflammation.Method: This comparative cross-sectional study was conducted at The Superior University, Lahore, over four months following ethical approval. A total of 98 adult patients (≥40 years) undergoing uncomplicated cataract surgery were enrolled using a non-probability purposive convenience sampling technique. Participants were equally divided into two groups: one receiving Nepafenac and the other receiving Bromfenac. This study included patients of senile cataract, post-operative ocular inflammation confirmed on slit lamp examination, and best-corrected visual acuity of 20/200 or better. Baseline assessments included slit lamp and fundoscopic examination. After surgery, participants were prescribed either Nepafenac or bromfenac and followed up at one week and one month to assess control of inflammation. Data were recorded using a structured proforma and analyzed using the chi-square and Fisher’s Exact tests to determine the significance of differences between the two treatment groups in SPSS-26 version. A p-value less than 0.05 was considered significant.Result: A total of 98 patients were enrolled in the study with a mean age of 65.92 ± 8.36 years. Bromfenac showed significantly better early postoperative anti-inflammatory effects compared to Nepafenac. On Day 1, patients in the Bromfenac group reported less pain (p < 0.001), less redness (p = 0.027), milder anterior chamber (AC) cell reactions (p < 0.001), and a lower incidence of vitritis (p < 0.001). The difference in AC cell reactions remained significant on Day 40 (p = 0.022). While both groups showed complete resolution of pain and vitritis by Day 40, 10.2% of Nepafenac patients still had mild AC cells. The difference was statistically significant (p = 0.022). Clinically, this suggests a slightly better long-term anti-inflammatory effect of Bromfenac.Conclusion: The study concluded that Bromfenac was more effective than Nepafenac in controlling early postoperative inflammation, particularly on Day 1, with significantly lower levels of pain, AC cells, and vitritis. While some differences persisted on Day 7, by Day 40, inflammation had resolved in all patients, and no significant differences remained between the groups.